utility of Immunological Marker CD14 in Identifying Monocytic Component in Acute Leukaemia - Tahir, Muhammad; Anwar, Masood; Raziq, Fazal (Journal of Postgraduate Medical Institute, 2011)
To assess the usefulness of immunological marker CD 14 in identifying malignant cells of monocytic lineage. Eight thin smears each from peripheral blood and bone marrow of seventeen acute leukaemia patients were obtained. Romandosky dye (Leishman) and cytochemical stains (Peroidase, Periodic acid Schiff, non specific esterase) were applied. Two bone marrow smears were then treated with immunological marker CD 14. CD 14 surface marker is a useful tool for identifying monocytic componet in neoplastic cells of acute leukaemia patients.